2019
DOI: 10.1039/c8py01777h
|View full text |Cite
|
Sign up to set email alerts
|

Reactive block copolymers for patterned surface immobilization with sub-30 nm spacing

Abstract: Reactive polystyrene-block-polyisoprene copolymers are synthesized by nitroxide-mediated polymerization, self-assemble within ultra-thin films, and exhibit surface reactivity for patterned immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…First and foremost, this is the first system which has been shown to yield nanoparticles with internal nanostructuration by SORP . Secondly, we recently pioneered SG1 nitroxide‐mediated polymerization (NMP) as a straightforward route for the synthesis of functional PS‐ b ‐PI with reasonable dispersity . Using NMP permits to avoid traditional, yet more complicated and less functional group‐tolerant protocols based on ionic polymerization and post‐polymerization modification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, this is the first system which has been shown to yield nanoparticles with internal nanostructuration by SORP . Secondly, we recently pioneered SG1 nitroxide‐mediated polymerization (NMP) as a straightforward route for the synthesis of functional PS‐ b ‐PI with reasonable dispersity . Using NMP permits to avoid traditional, yet more complicated and less functional group‐tolerant protocols based on ionic polymerization and post‐polymerization modification.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of functional groups in the PS block was kept rather low (<10 mol%) so as to impart functionality, while presumably not perturbing the phase separation behavior of the original PS‐ b ‐PI scaffold. This is based on our observations of a similar set of BCPs, which revealed that in the solid state these BCPs lead to lamellar morphologies with only minor changes in the interlamellar distance …”
Section: Resultsmentioning
confidence: 99%
“…For all experiments, we employed rather commonly encountered values in the field for the following parameters: Although it may not be the optimal ratio, we concentrated our investigations on copolymerizing 5 mol% of styrenics because (i) it was found that a rather decent control could be achieved with 4.4-8.8 mol% styrene 31 and (ii) it fits well our general goal of imparting side-chain reactivity to (block) copolymers without strongly altering their physical properties. [45][46][47] Kinetics and macromolecular control in solution…”
Section: Resultsmentioning
confidence: 99%
“…The final copolymers are particularly interesting in the development of reactive nanostructured materials based on phase-separating block copolymers involving low fractions of reactive comonomers. [45][46][47] In brief, the goal of the present article, rather than to provide an in-depth rate constant-based investigation, is to exemplify in a practical manner the opportunity to control the polymerization of methacrylates by SG1-mediated polymerization, while introducing functionality without strongly compromising initial physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate it would be more straightforward and economical to employ well‐known nanostructuring BCPs and introduce functionality by simple statistical copolymerization within each block. We have recently shown that polystyrene‐ block ‐polyisoprene (PS‐ b ‐PI) BCPs with a small amount (<5 mol%) of chloride, azide, or pentafluorophenyl functionality in the PS block are able to self‐assemble in a very similar manner with minor influence of the functional comonomer . However, the PI block is not particularly flexible in terms of functionalization.…”
Section: Introductionmentioning
confidence: 99%